On coupling fluid plasma and kinetic neutral physics models. (August 2017) - Joseph, I.; Rensink, M.E.; Stotler, D.P.; Dimits, A.M.; LoDestro, L.L.; Porter, G.D.; Rognlien, T.D.; Sjogreen, B.; Umansky, M.V.
Highlights: The Courant-Friedrichs-Lewy stability criterion restricts explicit plasma-neutral coupling methods to short time step. Residuals decay with particle number and increase with grid size with the same scaling predicted for nonlinear bias error. Progress is reported on implementation of a fully implicit Jacobian-free Newton-Krylov coupling scheme. Abstract: The coupled fluid plasma and kinetic neutral physics equations are analyzed through theory and simulation of benchmark cases. It is shown that coupling methods that do not treat the coupling rates implicitly are restricted to short time steps for stability. Fast charge exchange, ionization and recombination coupling rates exist, even after constraining the solution by requiring that the neutrals are at equilibrium. For explicit coupling, the present implementation of Monte Carlo correlated sampling techniques does not allow for complete convergence in slab geometry. For the benchmark case, residuals decay with particle number and increase with grid size, indicating that they scale in a manner that is similar to the theoretical prediction for nonlinear bias error. Progress is reported on implementation of a fully implicit Jacobian-free Newton–Krylov coupling scheme. The present block Jacobi preconditioning method is still sensitive to time step and methods that better precondition the coupled system are under investigation.